Pentingnya Guru Pendidikan Agama Kristen Dalam Pembentukan Karakter, Spritual, Moralitas Dan Rohani Peserta Didik - Hendra Agung Saputrsa Samaloisa; Hasahatan Hutahaean (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
This paper describes the importance of Christian Religious Education teachers in the formation of the character, spirituality, morality and spirituality of students. Christian religious education teachers play a very important role in the formation of the character, spirituality, morality and spiritual life of students. Here are some reasons why the role of the Christian religious education teacher is so important. Teaching Christian Values: Christian religious education teachers are responsible for teaching students about Christian teachings, such as love, forgiveness, loyalty, justice, and humility. Through this teaching, the teacher helps students understand the values that are important in Christian life and how to apply them in everyday life. Character Formation: Christian religious education helps in shaping the character of students. Through teaching and examples given by teachers, students learn about integrity, discipline, responsibility, hard work, and respect for others. All of this helps students develop strong and moral characters. The importance of Christian religious education teachers in the formation of character, spirituality, morality, and the spiritual life of students cannot be underestimated. Their role is to help prepare students to become individuals with integrity, have a strong moral foundation, and be able to face life's challenges with solid Christian beliefs.